Experimental suprachoroidal plombage with a urethane based hydrophilic polymer. Issue 4 (April 1988) - Foulds, W. S.; Aitken, D.; Lee, W. R.
Abstract : Small portions of dehydrated hydrophilic polymer (HPU 90, Smith and Nephew) have been inserted into the suprachoroidal space in rabbits to investigate the possible use of suprachoroidal plombage in retinal detachment surgery. As it hydrates, the material causes a pronounced elevation of choroid and retina, and the implants have been well tolerated for periods of up to one year in experimental animals. The implant slowly breaks down and stimulates a simple macrophagic reaction: fibrosis in the overlying choroid is associated with ischaemic gliosis and chorioretinal fusion.